Pengaruh Self-Efficacy terhadap Kemandirian Belajar Siswa pada Kompetensi Keahlian Akuntansi di SMK Muhammadiyah Kalianda - Haifani, Maharani Fadhiyah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aims to determine the effect of self-efficacy on students’ learning independence in the accounting competency program at SMK Muhammadiyah Kalianda. The research employed a quantitative approach with an ex post facto research design. The research subjects were eleventh-grade students selected using a total sampling technique. Data were collected through self-efficacy and learning independence questionnaires that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics and simple linear regression analysis. The results showed that students’ self-efficacy levels ranged from moderate to good, while students’ learning independence was categorized as fairly good. The regression analysis indicated that self-efficacy had a significant effect on students’ learning independence. Students with high levels of self-efficacy tend to be more confident, able to manage their learning processes independently, and more responsible for their academic tasks. These findings suggest that strengthening self-efficacy through teacher support and a positive learning environment is important for enhancing vocational students’ learning independence.